A Synthetic Hydrogel Composite with a Strength and Wear Resistance Greater than Cartilage. (4th August 2022) - Zhao, Jiacheng; Tong, Huayu; Kirillova, Alina; Koshut, William J.; Malek, Andrew; Brigham, Natasha C.; Becker, Matthew L.; Gall, Ken; Wiley, Benjamin J.
Abstract: Key hurdles for replacing damaged cartilage with an equivalent synthetic construct are the development of a hydrogel with a strength that exceeds that of cartilage and fixation of this hydrogel onto the surface of an articulating joint. This article describes the first hydrogel with a tensile and compressive strength (51 and 98 MPa) that exceeds those of cartilage (40 and 59 MPa), and the first attachment of a hydrogel to a metal backing with a shear strength (2.0 MPa) that exceeds that of cartilage on bone (1.2 MPa). The hydrogel strength is achieved through reinforcement of crystallized polyvinyl alcohol with bacterial cellulose. The high attachment strength is achieved by securing freeze‐dried bacterial cellulose to a metal backing with an adhesive and a shape memory alloy clamp prior to infiltration and crystallization of the polyvinyl alcohol. The bacterial cellulose‐reinforced polyvinyl alcohol is three times more wear resistant than cartilage over one million cycles and exhibits the same coefficient of friction. These advances in hydrogel strength and attachment enable the creation of a hydrogel‐based implant for durable resurfacing of damaged articulating joints. Abstract : This article describes the first hydrogel with a tensile and compressive strength that exceeds those of cartilage and the first attachment of a hydrogel to a metal backing with a shear strength that exceeds that of cartilage on bone. These advances in hydrogel strength and attachment enable the creation of a hydrogel‐based implant for durable resurfacing of damaged articulating joints.